2014
DOI: 10.1002/hfm.20543
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Injury Occurrence in Motor Vehicle Collision Using Artificial Neural Networks

Abstract: Vehicle collisions amount to a significant loss of life in America. Upward of 30,000 lives are lost each year in the United States alone. Hundreds of millions of dollars are spent each year on vehicle safety and roadway design in the United States, and many studies have been conducted on the causal factors for vehicle collisions. This study used artificial neural networks as a means to predict the occurrence of injury of a vehicle collision. The objective was to classify the levels of the “injury occurrence” i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…However, the area under curves for ROC plots shows very close prediction accuracy for class 1 and 3 (no injury and fatality), and less accuracy for class 2 (injury), this could be due to the fact that minor and major injuries were used undistinguishably with small dataset size for major injury cases. However, the overall prediction accuracy is considered acceptable and promising compared with previous literature such as [11,22,28,45]. In these studies, the ANN prediction accuracy ranged between 55% and 65%.…”
Section: Artificial Neural Networkmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the area under curves for ROC plots shows very close prediction accuracy for class 1 and 3 (no injury and fatality), and less accuracy for class 2 (injury), this could be due to the fact that minor and major injuries were used undistinguishably with small dataset size for major injury cases. However, the overall prediction accuracy is considered acceptable and promising compared with previous literature such as [11,22,28,45]. In these studies, the ANN prediction accuracy ranged between 55% and 65%.…”
Section: Artificial Neural Networkmentioning
confidence: 75%
“…Several studies used this particular type of ANN to investigate crashes risk factors. To name a few, [22] used a feedforward backpropagation ANN model to predict the occurrence of injuries in vehicle collision crashes in Florida. It was found that number of lanes and road surface conditions contribute the most to the injury occurrence.…”
Section: Decision Trees and Artificial Neural Network Onmentioning
confidence: 99%